Atmospheric water harvester-assisted solar steam generation for highly efficient collection of distilled water. Issue 4 (11th January 2022) - Dong, Suwei; Xu, Yunfan; Wang, Chenjie; Liu, Cihui; Zhang, Jinlei; Di, Yunsong; Yu, Liyan; Dong, Lifeng; Gan, Zhixing
Abstract : Solar steam generation (SSG) is developed as a promising way for seawater desalination and wastewater purification, bringing new opportunities for solving the shortages of freshwater. Abstract : Solar steam generation (SSG) is developed as a promising way for seawater desalination and wastewater purification, bringing new opportunities for solving the shortages of freshwater. Herein, hierarchical columnar RGO bundles with cold evaporation surfaces are designed for high-performance SSG. We find that the evaporation rate can be significantly increased by simply enlarging the dark evaporation area due to the enhanced extraction of energy from the ambient environment. Under one sun irradiation, an extremely high evaporation rate of 4.0 kg m −2 h −1 is obtained by disintegrating the RGO bundles into separated thin scrolls. However, the resulting vapor is not hot enough to be collected by condensation, which has been overlooked previously. To overcome this flaw, an atmospheric water harvester (AWH) is developed by impregnating LiCl salts and carbonized loofah powder (CLP) into a porous hydrogel. The AWH can not only effectively collect the cold vapor but also further improve the water evaporation rate. AWH assisted SSG is used for seawater desalination. The clean water collection rate reaches 2.1 kg m −2 h −1, which is a very competitive performance. And the salinity of the desalinated water is far lower than the standard of potable water set by the World Health Organization (WHO).